Legumes Research Volume 2 - Jimenez-Lopez, Jose C.; Clemente, Alfonso (IntechOpen, 2022)
Legumes have nutraceutical qualities that impart beneficial effects on human health. They are an alternative protein source with great potential for use in producing novel foods with improved nutritional properties. This book presents a comprehensive overview of legume proteins, including information on their nutritional and nutraceutical profiles, the health benefits of their compounds, and their underlying bioactivities such as anti-diabetic, hepatoprotective, anti-inflammatory, antioxidant, and anti-cancer properties.